(3EOGQI GdLhOI GdTGedI HefXeGJ GdQYGjI GdGLJeGYjIs - (3eMeO(B, (3YHO GdaJGM eMeOs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2008)
(3eaGgje h SeGJ h NUGFU h CgOGa GdefXeGJ GdGLJeGYjI eY eaghe GdLeYjGJ GdGgdjI JUfjaGJgG h CgejI OQGSI GdLeYjGJ aj GdNOeI GdGLJeGYjI h NUGFU GdLeYjGJ GdGgdjI GdeYGUQI , adSaJgG , JfXjegG GdGOGQj h ETcGdjGJgG , NUGFU h CgOGa fXGe GdMce aj eUQ h GdYdGbI Hjf GdefXeGJ GdGgdjI h GdMchejI , GdeTcdGJ GdGOGQjI ddefXeGJ GdGLJeGYjI eY JfGhd ehVhY GdGOGQI aj GdNOeI GdGLJeGYjI h GdGSS GdfXQjI dGOGQI GdLhOI GdTGedI eY feGPLgG h eQGMdgG , GdJfXje GdGOGQj h GdJNWjW GdGOGQj , GdJOQjH h JfejI GdYGedjf , GdJehjd h GdejRGfjI h CNjQG GdJWQb Gdi ehVhY GJNGP GdbQGQ(B.s
Keywords: (3GdEjRhs; (3GdGOGQIs; (3GdNOeI GdELJeGYjIs; (3VHW GdLhOIs